A survey of handling and transportation of UK farmed deer. (14th March 2023) - Pearce, Samuel J; Foster, Aiden P.; Knowles, Toby G; Statham, Poppy
Abstract: Studies on the transport of deer ( Cervidae ), in the UK, were published > 15 years ago. A more recent study of deer transport is required to allow for assessments and improvements to the transport of farmed deer. Sixteen deer farmers participated in a survey describing their management practices related to transport. Their responses showed that most vehicles used to transport deer were designed for other livestock. Participating farmers estimated journey times to slaughter as 1–8 h, with an arithmetic mean of 4.8 (± 2.38) h. Specific concerns raised by the respondents, relating to the transport of deer, included a need for deer-specific vehicles, stop-off areas for long journeys, market locations and haulier experience. Furthermore, data were collected from two abattoirs between July 2019 and June 2020 comprising journey times, slaughter times, bruising, location of origin, vehicle type and the number of animals. In total, 4, 922 deer were transported across 133 journeys (from farm to abattoir) from 61 farms. Median and range for journey length were 3.2 (0.4–9.8) h and 154.2 (7.1–462.2) km, whereas group size and time spent in the lairage were 24 (1–121) and 17.8 (10.2–68.9) h, respectively. Group size was found to be significantly associated with both the presence of bruising in a group and the amount of bruising per deer. This study provides a much-needed update on the transport of farmed deer in the UK and highlights key areas for future research including the welfare impact of transport in larger groups and for longer durations.